Review of the epidemiology and variability of LRRK2 non-p.Gly2019Ser pathogenic mutations in Parkinson’s disease - Turski, Paweł; Chaberska, Iwona; Szukało, Piotr; Pyska, Paulina; Milanowski, Łukasz; Szlufik, Stanisław; Figura, Monika; Hoffman-Zacharska, Dorota; Siuda, Joanna; Koziorowski, Dariusz (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is a heterogenous neurodegenerative disorder. Genetic factors play a significant role, especially in early onset and familial cases. Mutations are usually found in the LRRK2 gene, but their importance varies. Some mutations, such as p.Arg1441Cys or other alterations in the 1441 codon, show clear correlation with PD, whereas others are risk factors found also in healthy populations or have neglectable consequences. They also exhibit various prevalence among different populations. The aim of this paper is to sum up the current knowledge regarding the epidemiology and pathogenicity of LRRK2 mutations, other than the well-established p.Gly2019Ser. We performed a review of the literature using PubMed database. 103 publications met our inclusion criteria. p.Arg1441Cys, p.Arg1441Gly, p.Arg1441His, p.Arg1441Ser are the most common pathogenic mutations in European populations, especially Hispanic. p.Asn1437His is pathogenic and occurs mostly in the Scandinavians. p.Asn1437Ser and p.Asn1437Asp have been reported in German and Chinese cohorts respectively. p.Ile2020Thr is a rare pathogenic mutation described only in a Japanese cohort. p.Met1869Thr has only been reported in Caucasians. p.Tyr1699Cys, p.Ile1122Val have only been found in one family each. p.Glu1874Ter has been described in just one patient. We found no references concerning mutation p.Gln416Ter. We also report the first case of a Polish PD family whose members carried p.Asn1437His.